Beyond Control A Mutual Respect Approach to Protest Crowd - Police Relations - Paré, Shirley (Bloomsbury Academic, 2010)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. What is refreshing about Beyond Control is the vision for the kind of society in which protestors and police recognize their mutual humanity as well as how both are needed for a democratic society to function well. ' From the Foreword by Archbishop Desmond Tutu How can large protest crowds be better and more respectfully managed by police? This topical book applies the principles of community-based conflict resolution to the policing of large crowds, suggesting a completely new approach that moves away from the discourse of rabble-rousing mobs towards negotiated management, and a paradigm of mutual respect for protesters as principled dissenters and for police as non-repressive agents of public order. Both are needed, the authors argue, in order for democracy to flourish.